Menumbuhkan Karakter Religius Pada Anak Usia Dini Melalui Kisah Nabi Ayyub a.s - Maula, Inayatul; Parapat, Asmidar (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
Tells the story of a prophet is one appropriate method to help foster a child's character andpersonality that can serve as an example or a reflection in their everyday lives. This method isrelevant if it is used to instill Islamic character in early childhood, as they are in recognizing thevalue of the character is still using his imagination. In the story of Prophet Ayyub as. Educatorsexpect to early childhood in order to take a lesson or moral of the story that can inspire childrento diterapkkan in everyday life.Through the story of Prophet Ayyub as. Expected to Growattitude of patience and gratitude in children so that it will provide an opportunity for childrento think, feel, reflect on the story, so as if he had a role in the story. Their emotional connectionto the story or stories of children would provide opportunities for children to take the exampleof the figures who have a certain kind and tried to leave the depraved behavior